Rancangan Alat Elektroplating dan Eksperimen Pelapisan Berbahan CuSO4 Terhadap Ketebalan Lapisan - Nurhilal, Mohammad; Ratri Harjanto, Taufan; Bahri, Saipul; Purwiyanto, Purwiyanto (Infotekmesin, 2021)
The electroplating method has the aim of producing a surface that has characteristics by the coating metal. The coating process requires a device that can place the ions from the coating material (anode) into the coated metal (cathode) through an electro-deposition process. Parameters such as temperature affect the electroplating process and greatly determine the coating result. The purpose of this study was to design the electroplating device, as well as to test the coating process using CuSO4 anode. The research method was carried out with an experimental approach through the manufacture of electroplating tools and coating testing of time variations of 20, 26, 32, 38, and 44 minutes and temperatures of 60, 65, 70, 75, and 80 oC. The results of the electroplating device design consist of frame components, plating and rinsing tubs, electrical systems, and cathode hanger. The coating results obtained the highest layer thickness 2.890 Î¼m at a temperature of 80 oC for 40 minutes.